Cochlear implants: our experience and literature review - Martins, Mariane Barreto Brandão; de Lima, Francis Vinicius Fontes; Santos, Ronaldo Carvalho, Júnior; Santos, Arlete Cristina Granizo; Barreto, Valéria Maria Prado; de Jesus, Eduardo Passos Fiel (International Archives of Otorhinolaryngology, 2012)
Introduction: Cochlear Implants are important for individuals with severe to profound bilateral sensorineural hearing loss.Objective: Evaluate the experience of cochlear implant center of Otorhinolaryngology through the analysis of records of 9 patients who underwent cochlear implant surgery.Methods: This is a retrospective study performed with the patients records. Number 0191.0.107.000-11 ethics committee approval. We evaluated gender, etiology, age at surgery, duration of deafness, classification of deafness, unilateral or bilateral surgery, intraoperative and postoperative neural response and impedance of the electrodes in intraoperative and preoperative tests and found those that counter-indicated surgery.Results: There were 6 pediatric and 3 adult patients. Four male and 5 female. Etiologies: maternal rubella, cytomegalovirus, ototoxicity, meningitis, and sudden deafness. The age at surgery and duration of deafness ranged from 2–46 years and 2–18 years, respectively. Seven patients were pre-lingual. All had profound bilateral PA. There were 7 bilateral implants. Intraoperative complications: hemorrhage. Complications after surgery: vertigo and internal device failure. In 7 patients the electrodes were implanted through. Telemetry showed satisfactory neural response and impedance. CT and MRI was performed in all patients. We found enlargement of the vestibular aqueduct in a patient and incudomalleolar malformation.Conclusion: The cochlear implant as a form of auditory rehabilitation is well established and spreading to different centers specialized in otoaudiology. Thus, the need for structured services and trained professionals in this type of procedure is clear.
Keywords: cochlear implants; hearing loss; hearing loss; sensorineural